2014
DOI: 10.2991/ijndc.2014.2.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Human Activity Recognition in WSN: A Comparative Study

Abstract: Human activity recognition is an emerging field of ubiquitous and pervasive computing. Although recent smartphones have powerful resources, the execution of machine learning algorithms on a large amount of data is still a burden on smartphones. Three major factors including; classification algorithm, data feature, and smartphone position influence the recognition accuracy and time. In this paper, we present a comparative study of six classification algorithms, six data features, and four different positions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Therefore, it is essential that studies collect data from as many body locations as possible to ensure the generalizability of results. In the reviewed literature, study participants were often instructed to carry the device in a pants pocket (either front or back), although a number of studies also considered other placements, such as jacket pocket 46 , bag or backpack 47 , 48 , and holding the smartphone in the hand 49 or in a cupholder 50 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is essential that studies collect data from as many body locations as possible to ensure the generalizability of results. In the reviewed literature, study participants were often instructed to carry the device in a pants pocket (either front or back), although a number of studies also considered other placements, such as jacket pocket 46 , bag or backpack 47 , 48 , and holding the smartphone in the hand 49 or in a cupholder 50 .…”
Section: Resultsmentioning
confidence: 99%
“…The desired performance optimum was obtained by making use of dataset remodeling (e.g., by replacing the oldest observations with the newest ones), low-cost classification algorithms, limited preprocessing, and conscientious feature selection 45,86 . Computation time was sometimes reported for complex methods, such as deep neural networks 20,82,111 and extreme learning machine 112 , as well as for symbolic representation 85,86 and in comparative analyses 46 . A comprehensive comparison of results was difficult or impossible, as discussed below.…”
Section: Activity Classificationmentioning
confidence: 99%
“…This section presents some state-of-the-art studies that have been used for real-time sensor data segmentation (i.e., in knowledge-driven [7,24], data-driven [1,17], or hybrid [8,38] approaches) and highlight some literature in activity learning so that the inferred knowledge can also be considered during the segmentation stage. The common characteristics that are used to separate the data stream are time, location, sensor type (i.e., temperature, humidity, touch), and value (binary, float, decimal, string) [5].…”
Section: Related Workmentioning
confidence: 99%
“…Based on the study [3], it can be concluded that certain statistical features give an insight regarding the data pattern of an activity. The data pattern analysis is an approach that can be used to divide the activities into various groups.…”
Section: Introductionmentioning
confidence: 99%
“…A similar kind of study to compare statistical features that are typically extracted from the sensors' raw data, and on classification algorithms, which are used to construct classification models, was done in [3], to examine the data behavior. Based on the study [3], it can be concluded that certain statistical features give an insight regarding the data pattern of an activity.…”
Section: Introductionmentioning
confidence: 99%